Peculiarities Of Teaching Reading at Higher Educational Institutions (Eurasian Scientific Herald, 2022)
The relevance of reading should be overestimated, in today’s modern world there is a vital need for instructors working at higher educational institutions to get acquainted with both modern theoretical approaches to teaching reading and practical experience - in different educational contexts, in different foreign languages, for different purposes and learning objectives. This article observes the main purpose of reading and teaching methods of the skill